2018
DOI: 10.5152/turkpediatriars.2017.5511
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patients with orbital infections

Abstract: Aim: Orbital tissue infections are common infections of childhood that can lead to severe complications. Herein, we aimed to evaluate the etiologic factors, diagnosis, follow-up, and treatment procedures in pediatric patients with orbital infections. Material and Methods:This study was performed retrospectively between January 2014 and December 2015 in Cerrahpasa Medical Faculty Pediatric Infectious Disease Unit. Patients were studied for age, ophthalmologic examination features, laboratory and radiology resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
(19 reference statements)
1
6
1
1
Order By: Relevance
“…In the series of Botting et al consisting of 262 pediatric patients with periorbital infection, the frequency of preseptal cellulitis and orbital cellulitis were found 87% and 13% [5]. In studies performed in our country reported that the frequency of preseptal cellulitis is between 81% and 88.9%, the frequency of orbital cellulitis is between 11.9% and 19% in admitted children with periorbital infections [14,15]. The similarly ratio of preseptal cellulitis and orbital cellulitis detected in our study.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…In the series of Botting et al consisting of 262 pediatric patients with periorbital infection, the frequency of preseptal cellulitis and orbital cellulitis were found 87% and 13% [5]. In studies performed in our country reported that the frequency of preseptal cellulitis is between 81% and 88.9%, the frequency of orbital cellulitis is between 11.9% and 19% in admitted children with periorbital infections [14,15]. The similarly ratio of preseptal cellulitis and orbital cellulitis detected in our study.…”
Section: Discussionsupporting
confidence: 62%
“…The age of the patients with orbital involvement was larger than that of the patients without orbital involvement in our study, but this difference was not statistically signi cant. Male gender was found to be more frequent in patients with or without orbital involvement [5,15]. While the male/female sex ratio was 1.4/1 in orbital involvement, it was 1.5/1 in our patients with preseptal cellulitis cases.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Yapılan birçok çalışmada, başlangıç antibiyotik tedavisi olarak ampisilin-sulbaktam veya 3. kuşak sefalosporinlere klindamisin, metronidazol gibi anaeroplara etkili ajanların eklenmesiyle etkili bir tedavi sağlandığı vurgulanmıştır. 13,14 Benzer şekilde, bizim kliniğimizde de rutin olarak seftriakson ve metronidazol kombinasyonu uygulanmaktadır. Enfeksiyon hastalıkları kliniğinin önerisi doğrultusunda üç hastaya seftriakson, amikasin ve bir hastaya seftriakson, klindamisin tedavisi uygulanmıştır.…”
Section: Discussionunclassified